2015
DOI: 10.1002/mnfr.201500110
|View full text |Cite
|
Sign up to set email alerts
|

Blood micronutrients and DNA damage in children

Abstract: DNA damage in healthy children may be influenced by blood micronutrient levels and certain genotypes. Further investigation of associations between nutritional status and genomic integrity in children is needed to shed additional light on potential mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…Similar scenarios have also been observed for deficiencies in vitamin B-12, riboflavin, vitamin A, and minerals such as calcium and zinc (99). Conversely, supplementation with folic acid (97, 100-108), riboflavin, pantothenic acid, biotin (4), cobalamin (93,103), vitamin C (109)(110)(111)(112)(113)(114)(115), vitamin E (114), and vitamin A and its derivatives (107,112) was associated with decreased genotoxic damage and micronucleus reduction (4). Much research has been conducted to show the effects of folic acid supplementation and folate status on reduced micronucleus frequency.…”
Section: Micronutrients and Chromatin Instabilitymentioning
confidence: 61%
“…Similar scenarios have also been observed for deficiencies in vitamin B-12, riboflavin, vitamin A, and minerals such as calcium and zinc (99). Conversely, supplementation with folic acid (97, 100-108), riboflavin, pantothenic acid, biotin (4), cobalamin (93,103), vitamin C (109)(110)(111)(112)(113)(114)(115), vitamin E (114), and vitamin A and its derivatives (107,112) was associated with decreased genotoxic damage and micronucleus reduction (4). Much research has been conducted to show the effects of folic acid supplementation and folate status on reduced micronucleus frequency.…”
Section: Micronutrients and Chromatin Instabilitymentioning
confidence: 61%
“…By contrast, another study evaluating the effect of supplementation with 100 μM Zn sulfate showed that human lymphocyte viability was not affected (Sliwinski et al 2009). Elevated MNi frequency in lymphocytes has been shown to be associated prospectively with an increased risk of cancer in a cohort study, with severe adverse cardiovascular events in coronary artery disease patients and with mortality from cancer or cardiovascular disease in a case-control study (Milne et al 2015).…”
Section: Discussionmentioning
confidence: 94%
“…For the study we chose method for blood cell cultivation with cytochalasine B usually used for detection of micronuclei in binuclear cells [16]. In this study we wide the ability of the method, taking into consideration, practically, all types of cells, micronuclei in them, apoptosis and mitotic activity ( Figure 4).…”
Section: Human Emotional Stress and Environmental Pollutionmentioning
confidence: 99%
“…This experimental approach is directed mainly to the evaluation of the activity of apoptosis, because the role of the low-priming-dose of ionizing radiation, which itself, practically, doesn't induce detectable levels of genetic damage, is, mostly, to induce apoptosis [10]- [16].…”
Section: Human Emotional Stress and Environmental Pollutionmentioning
confidence: 99%
See 1 more Smart Citation